VARIABILITY, CORRELATION AND PATH ANALYSIS FOR SEED YIELD AND ITS COMPONENT TRAITS IN BIDI TOBACCO (Nicotiana tabacum L) - J. MANJUNATH, Y. BHARATHI, S. JAFFARBASHA and (The Journal of Research, PJTSAU, 2019)
Due to the growing awareness of alleged health risk factors associated with tobaccos conventional uses, research efforts need to be geared up for alternative uses of tobacco. Patel et al., 1985 reported that it is possible to make use of tobacco crop for the production of several agro based chemicals. Apart from these, tobacco plant also produces oil rich seeds. Tobacco plays a prominent role in the Indian economy. Tobacco seed oil is reported to be used in certain pharmaceutical preparations, in alkyd resins and in soap manufacture. It is also used as edible oil after suitable refining in Greece, Bulgaria and some other countries (Somayajulu and Murti, 1963).